2021
DOI: 10.2147/ndt.s283731
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Measurement-Based Care for Depression: Practical Solutions for Psychiatrists and Primary Care Physicians

Abstract: Measurement-based care (MBC) can be defined as the clinical practice in which care providers collect patient data through validated outcome scales and use the results to guide their decision-making processes. Despite growing evidence supporting the effectiveness of MBC for depression and other mental health conditions, many physicians and mental health clinicians have yet to adopt MBC practice. In part, this is due to individual and organizational barriers to implementing MBC in busy clinical settings. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“…6,9,10 MBC includes (1) routine administration of validated rating scales, either by clinician-rated or patient-reported outcomes (PROs); (2) review of scores by practitioners and patients; and (3) using scores to inform shared clinical decision-making. 11,12 MBC has specifically been recommended for the management of MDD by the American Psychiatric Association (APA), 13 Canadian Network for Mood and Anxiety Treatments (CANMAT), 14 and UK National Institute for Health and Care Excellence (NICE) 15 clinical practice guidelines.…”
mentioning
confidence: 99%
“…6,9,10 MBC includes (1) routine administration of validated rating scales, either by clinician-rated or patient-reported outcomes (PROs); (2) review of scores by practitioners and patients; and (3) using scores to inform shared clinical decision-making. 11,12 MBC has specifically been recommended for the management of MDD by the American Psychiatric Association (APA), 13 Canadian Network for Mood and Anxiety Treatments (CANMAT), 14 and UK National Institute for Health and Care Excellence (NICE) 15 clinical practice guidelines.…”
mentioning
confidence: 99%
“…Measurement-based care (MBC)the routine use of simple, validated outcome scales such as the Patient Health Questionnaire (PHQ-9) depression scale [6] to guide clinical decision-making in treating MDDis an EBP that may help meet these ambitious objectives [7]. The self-rated PHQ-9 can be helpful in screening, diagnosis and monitoring treatment; in primary care and other settings, the PHQ-9 can increase the recognition of MDD and improve outcomes when used within an MBC management approach [7]. For example, simple algorithms based on PHQ-9 scores can help physicians decide when to change the dose of an antidepressant or when to switch to another [7,8].…”
Section: Of 16mentioning
confidence: 99%
“…The self-rated PHQ-9 can be helpful in screening, diagnosis and monitoring treatment; in primary care and other settings, the PHQ-9 can increase the recognition of MDD and improve outcomes when used within an MBC management approach [7]. For example, simple algorithms based on PHQ-9 scores can help physicians decide when to change the dose of an antidepressant or when to switch to another [7,8]. Importantly, it can help identify which patients are not improving so that more intensive treatment can be offered.…”
Section: Of 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses of these studies have demonstrated that patients using smartphone apps show a greater improvement in symptoms vs. controls, with a greater effect when compared with inactive than active control conditions, encouraging the integration of MHApps into the treatment of important and common psychiatric illnesses [25,26]. Many of these tools empower patients by enabling them to track their progress and become active participants in their healthcare journeys [27]. Moreover, many apps serve as useful methods for monitoring and facilitating early identification of risk and thus help mitigate negative psychiatric outcomes [28].…”
Section: Introductionmentioning
confidence: 99%